CORRELATION BETWEEN MATERNAL FACTOR AND STUNTING AMONG CHILDREN OF 6-12 MONTHS OLD IN CENTRAL LOMBOK - Qurani, Ratu M.; Karuniawaty, Titi Pambudi; John, Ristania Ellya; Wangiyana, Ni Komang Ayu Swanitri; Setiadi, Qisthinadia Hazhiyah; Tengkawan, Jeslyn; Septisari, Ayu Anandhika; Ihyauddin, Zulfikar (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2022)
ABSTRACTBackground: Stunting is a child growth and development disorder that has been one of the nutritional problem in children living in developing countries until now. Maternal factor might be one of the risk factors of stunting. Method: This was an analytical observational study with cross sectional design that aimed to identify the correlation between the maternal factor and stunting, especially in children aged 6-12 months in 3 villages in Central Lombok. Result: There were 21,9% (33 of 151) of children suffering from stunting. Based on the maternal factor in stunting children, there were 6,1% of mothers who had low body mass index (BMI), 27,3% of mothers who had low arm circumference, 61% of mothers who had low weight gain during the pregnancy, and 39,4% of mothers who had height <150 cm. Maternal height was the only factor that significantly associated to the incidence of stunting (p = 0.044, OR = 2.3). Conclusion: Based on analysis of several maternal factors, there is a significant correlation between mother's height and stunting (p<0,05 and OR=2,3). ABSTRAKLatar Belakang: Stunting merupakan gangguan pertumbuhan dan perkembangan pada anak, yang sampai saat ini masih menjadi salah satu masalah gizi anak terutama di negara berkembang. Faktor maternal adalah salah satu faktor risiko stunting. Metode: Penelitian analitik observasional dengan rancangan cross sectional ini bertujuan untuk menganalisis hubungan antara faktor maternal dan stunting pada anak usia 6-12 bulan di 3 desa di Lombok Tengah. Hasil: Terdapat 21,9% (33 dari 151) anak yang mengalami stunting. Berdasarkan faktor maternal pada anak dengan stunting, sebanyak 6,1% memiliki ibu dengan indeks masa tubuh (IMT) rendah, 27,3% memiliki ibu dengan lingkar lengan atas rendah, 61% memiliki ibu dengan peningkatan berat badan yang rendah selama kehamilan, dan 39,4% memiliki ibu dengan tinggi badan <150 cm. Faktor tinggi badan ibu merupakan satu-satunya faktor yang berhubungan signifikan dengan kejadian stunting (p=0,044, OR=2,3). Kesimpulan: Berdasarkan analisis beberapa faktor maternal, terdapat hubungan yang signifikan antara tinggi badan ibu dan stunting (p<0,05 dan OR=2,3).